Symmetries and selection rules in photoelectron chiral dichroism - Ofer Neufeld (Proceedings of the National Academy of Sciences, 2025)
Photoelectron circular dichroism (PECD) is a method whereby randomly oriented chiral molecules are irradiated by circularly polarized light (CPL), photoionizing electrons, which are measured in a momentum-resolved manner. This scheme permits chiral light–matter interactions within the electric-dipole approximation (avoiding weak magnetic-dipole interactions), yielding huge chiral signals in the form of a forward–backward asymmetry in photoemission. Recently, more intricate realizations of PECD have been explored where the CPL is replaced with elaborate polarization-tailored light (e.g., bichromatic, noncollinear, etc.), some of which do not even require circularly polarized components, but still lead to massive chiral signals. However, the connection between generalized symmetries and asymmetries of the laser drive and selection rules in PECD have not yet been derived. Here, we formulate this connection analytically from group theory, also predicting two previously unknown selection rules for PECD from fields with dynamical inversion and improper-rotational symmetries. We further propose bichromatic bielliptical fields for breaking symmetries in typical spectra, yielding potentially more information for ultrafast-resolved measurements. We numerically demonstrate all of our results with state-of-the-art ab-initio simulations in the archetypal chiral molecule, Bromochlorofluoromethane, providing predictions for experiments. Our work presents a roadmap for analyzing PECD from tailored light and resolves a long-standing issue in the field. It should motivate theoretical and experimental investigations in novel PECD set-ups.